How different are soccer training sessions based on small-sided games? A cluster analysis to explore perceived exertion and training load - Marqués-Jiménez, D.; Sampaio, J.; Calleja-González, J.; Echeazarra, I. (Acta Gymnica, 2022)
Background: Soccer coaching staffs may have difficulties in classifying properly the load accomplished during training sessions and understanding how players rate the effort and the training load during the micro-cycles.